Biotechnological significance of Actinobacterial research in India. - Ballav, Shuvankar; Dastager, Syed; Kerkar, Savita (Recent Research in Science and Technology, 2012)
Actinobacteria are of special biotechnological interest since they are known to produce chemically diverse compounds with a wide range of biological activity. This distinct clade of Gram-positve bacteria include some of the key antibiotic producers and are also sources of several bioactive compounds, established commercially. The class Actinobacteria holds some of the resilient species, capable of growing in extreme, hostile and polluted environments. Their adaptation has been the outcome of several chemical entities which are answers to a number of medicinal and industrial questions of today. In India, actinobacterial research in both marine and terrestrial ecosystems has prospered significantly in past few decades. This valuable class contains large number of genera and demands more attention for exploration. Though substantial work in this field has been carried out, the diversity from the extreme environments in the Indian Peninsula remain unexplored. Marine actinobacterial research has been restricted to the coastal ecosystem while the deep sea oceanic floors remain untapped. Substantial bioprospecting of actinobacteria for bioactive molecules, has not been explored in extremophilic environments in India and the molecular mechanisms for the production of various bioactive compounds are yet to be reported. The present review enlists the prolific metabolites from culturable actinobacteria and attempts have been made to focus on the potentially feasible aspects of actinobacterial research in this field.